1997
DOI: 10.1046/j.1537-2995.1997.37297203525.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited utility of alanine aminotransferase screening of hepatitis C antibody‐screened blood donors

Abstract: With the introduction of HCV 2.0 screening. ALT appears to have little value as a surrogate test for hepatitis C, and ALT testing was unable to detect any donors who later seroconverted, as detected by HCV 2.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As a donor screening test, ALT has low specificity for detecting individuals with TTVI risk and is no longer used in routine donor screening in many countries. Because ALT elevation is not usually associated with HCV infection in the preseroconversion phase, it is likely that the abnormal ALT results for Samples 2 and 3 are unrelated to the HCV infection status of these donors 18‐20 …”
Section: Discussionmentioning
confidence: 99%
“…As a donor screening test, ALT has low specificity for detecting individuals with TTVI risk and is no longer used in routine donor screening in many countries. Because ALT elevation is not usually associated with HCV infection in the preseroconversion phase, it is likely that the abnormal ALT results for Samples 2 and 3 are unrelated to the HCV infection status of these donors 18‐20 …”
Section: Discussionmentioning
confidence: 99%
“…Many countries either do not have compulsory ALT testing for blood donors or use a high ALT cut-off value. 7,8 The aim of the current study was to investigate the prevalence of HEV antibodies and RNA in blood donors with elevated or normal ALT concentrations, and to determine whether there is a relationship between ALT concentration and HEV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of blood donor populations concluded that elevations of ALT correlated with the development of non‐A, non‐B hepatitis in transfusion recipients 1,2 . A large body of scientific data now exists that supports a conclusion that moderate ALT elevations in blood donors who are negative for all current transfusion‐transmitted disease markers are seldom due to acute or chronic viral hepatitis 3–7 . In January 1995, an NIH consensus panel considered ALT testing in the context of transfusion safety and evaluated whether its use should be continued.…”
mentioning
confidence: 99%